Contributions for a viable framework of conversion of debt into donation in Peru - Remy, Paul (1993)
The author describes donation debt swaps -one of the several menu options for debt treatment- and recent experiences in other countries. He proposes developing debt swaps basically for social and poverty relief spending, bearing in mind the in sufficiency of the actual amounts given today to such areas. T e paper underlines the advantages of donation debt swaps over debt reduction and of creating permanent funds for critical social areas. Finally, the author makes several suggestions for the scheme's appropriate development.